T. V. MOSEICHUK: LANGUAGE PORTRAIT OF THE PERSONALITY IN THE SPACE OF THE ARTISTIC TEXT: THE ROLE OF VERBALIZATION OF THE NON-VERBAL COMMUNICATION COMPONENT - MOSEICHUK, T. V. (Linguistic Bulletin (Movoznavchyi Visnyk), 2021)
Summary. Introduction. The realization of the author's intention, the disclosure of the characters of literary heroes is unthinkable without showing both the verbal and non-verbal behavior of the characters in various communicative situations. Рurpose. The purpose of the article is to reveal the role of verbalization of the non-verbal component of communication in the process of forming the linguistic personality of an artistic character in the space of a literary text (by the example of describing the non-verbal behavior of a master in M. Bulgakov’s novel “The Master and Margarita”). Results. The publication makes an attempt to identify the role of verbalizing the non-verbal component of communication in the process of forming the language personality of the character art in the space of the fiction text (for example descriptions of non-verbal behaviour of the master in the novel M. Bulgakov «Master and Margarita»). The lexical and syntactic features of the linguistic representation of the phonation and kinesic components of communication are traced, the interrelation of the phonational characteristics of speech, the gestural accompaniment of communication and the emotional state of the artistic character is revealed. Conclusion. Analysis of the linguistic representation of the incorrect behavior of the linguistic personality of an artistic character shows the dependence of the choice of phonation and kinesic means of NVK on the communicative situation, the composition of communicants, emotional; there are also noticeable differences in the choice of linguistic means, grammatical structures in the transmission of various elements of the NIAC. The prospect of further research requires significant expanded research, both in one area of one work or works of one author, and in the field of various directions, genres, time periods. At the same time, attention can be directed, firstly, to their comparative analysis, secondly, to a detailed study of the linguistic component of the verbalization of NVC in a literary text, thirdly, to identifying the systemic connections of non-verbal semiotics and communication theory, and fourthly, on instructions for classifications that maximally take into account lexical-grammatical, semiotic and communicative characteristics.